Analisis Return Metode Dogs Of The Dow dengan Uji-T Pada IDXHIDIV20 - Helynda Mulya Arga Retha; Retno Budiarti (ABEC Indonesia, 2022)
All investors should strive to beat the market, that is, get a higher return than the market return, which is usually represented by an index. Composite Stock Price Index is the name of the stock market index in Indonesia (IHSG). The "Dogs of the Dow" investment strategy steers the portfolio toward high-yield investments in an attempt to outperform the Dow Jones Industrial Average (DJIA) every year. The overall idea is to invest money in the top 10 stocks among the 30 DJIA components with the largest dividend yields. A company's ability to pay dividends provides insight into its value. Testing Dogs of The Dow begins with the selection of stocks with the highest dividend distribution. The author uses stock data recorded on (IDX High Dividend 20) which is accessed from idx.co.id. The author takes stock samples from this index because all of its stocks have distributed cash dividends every year for the last 3 years and have daily trading values in the regular market at least IDR 1 billion for the last 3 months, 6 months and 12 months. The Dogs of the dows strategy had pretty good results. This can be seen from the results of the average return calculation, where 8 of the 11 Dogs of the dows strategy data were able to beat the market returns, namely the JCI, namely in 2011, 2013, 2014, 2016, 2017, 2018, 2020, and 2021. in 2011 the average market return was at 1.16% while the Dogs of the dow strategy had a return of 1.34%. The biggest return was in 2016, where the Dogs of the dow strategy was able to reach 4.95%, while the average return from the JCI was only 1.30%.